High-technology manufacturing and U.S. competitiveness - Kelley, Charles, Jr.; Wang, Mark.; Bitko, Gordon; Chase, Michael S.; Kofner, Aaron; Lowell, Julia F.; Mulvenon, James C., 1970-; Ortiz, David Santana; Pollpeter, Kevin L.; Science and Technology Policy Institute (Rand Corporation); Rand Corporation; United States. Office of Science and Technology Policy (Santa Monica, CA : RAND, 2004)
In response to the concern that an increasing amount of high-technology manufacturing formerly performed in the United States is now being done overseas, the Office of Science and Technology Policy asked the RAND Corporation to provide analytic support to the President's Council of Advisors on Science and Technology. The support included a description of past and current trends of U.S. high-tech manufacturing, a theoretical and empirical economic analysis of traditional and high-tech manufacturing, and an analysis of U.S. research and development statistics and of trends in choices of academic disciplines.
Introduction -- U.S. Traditional and High-Technology Manufacturing: An Irreversible Decline? Does It Matter? -- Historical and Structural Effects on Market Share of Semiconductors in the United States -- Current Computer and Semiconductor Manufacturing Statistics -- U.S. Research and Development Statistics -- Science and Engineering Degree Statistics -- Cross-Strait Information Technology and Investment Flows, and Taipei's Policy Responses.
"March 2004."
"RAND Science and Technology."
Includes bibliographical references (p. 131-139).
Also available on the internet via WWW in PDF format.
Keywords: Competition, International; High technology industries -- Government policy -- United States; High technology industries -- United States; Semiconductor industry; Technology assessment -- Economic aspects -- United States